Implementasi Kebiri Kimia terhadap Pelaku Kejahatan Seksual Anak Ditinjau dari Hukum Pidana dan Hak Asasi Manusia - Yusuf, Zaharah Zanariah (Wajah Hukum, 2026)
The rising number of sexual violence cases against children has prompted the state to introduce chemical castration as an additional penalty within Indonesia’s criminal justice system. This policy has generated debate because it lies between the need to protect children and the state’s duty to uphold human rights. This study examines the judicial considerations in District Court Decision No. 5/Pid.Sus/2022/PN Bjm, which imposed chemical castration on a perpetrator of child sexual violence, and evaluates its application from the perspectives of criminal law and human rights. This research adopts a normative juridical method using statutory, conceptual, and case approaches by reviewing the 1945 Constitution, the Child Protection Law, Government Regulation No. 70 of 2020, the Human Rights Law, and relevant literature and case law. The findings show that the court imposed chemical castration based on the proven elements of the offense, the repeated nature of the acts, and the perpetrator’s position of authority as a stepfather. The policy is viewed as a preventive measure to reduce the risk of reoffending. However, its implementation raises human rights concerns due to potential interference with bodily integrity, inconsistency with medical ethics, and the absence of clear technical guidelines.